Mitosporic fungi from Sardar sarovar - Patil, S Y; Wagh, D D (International Multidisciplinary Research Journal, 2013)
The present paper deals with five species of Dematiaceous mitosporic fungi were collected from the submerged wood samples from the Sardar Sarovar region. Four species viz. Ellisembia plovercovensis Goh and Hyde, Monodictys trichocladiopsis Goh and Hyde, Neta angliae Hyde & Goh and Xylomyces elegans Goh, Ho, Hyde and Tsui are being recorded for the first time form India. Brief notes and illustration are given for each taxon. Geographical distribution of each species in India is also provided.